2020
DOI: 10.21037/apm-20-1389
|View full text |Cite
|
Sign up to set email alerts
|

Platelet to lymphocyte ratio as a prognostic factor in patients with advanced colorectal cancer undergoing palliative treatment

Abstract: Background: Our study aims to investigate the level of platelet to lymphocyte ratio (PLR) and determine its prognostic value in patients with advanced colorectal cancer undergoing palliative treatment.Methods: One hundred and fifty-two patients with advanced colorectal cancer confirmed in our hospital from January 2013 to January 2018 were selected as study participants. The boundary-value of PLR was determined by receiver operating characteristics (ROC) curves. Furthermore, the relationship between PLR and cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Also, platelets and PLR have been found to be independent prognostic factors for numerous solid tumors [ 39 ] including non-small cell lung cancer [ 36 ], hepatocellular carcinoma [ 12 ], renal cell carcinoma [ 32 ], breast cancer [ 13 ], colorectal cancer [ 40 ] and melanoma [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also, platelets and PLR have been found to be independent prognostic factors for numerous solid tumors [ 39 ] including non-small cell lung cancer [ 36 ], hepatocellular carcinoma [ 12 ], renal cell carcinoma [ 32 ], breast cancer [ 13 ], colorectal cancer [ 40 ] and melanoma [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, in rectal cancer, a worse prognosis has been associated with a lower lymphocyte/monocyte ratio prior to neoadjuvant treatment [ 28 ]. On the other hand, an elevated PLR has been described as a poor prognostic factor in advanced colorectal cancer [ 29 ]. In rectal cancer, an elevated PLR, also determined before CRT, has been shown to be a poor prognostic factor [ 30 ], sometimes together with the NLR [ 31 ], although this could not be confirmed in other studies [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…25 Serum albumin levels and BMI are common nutritional indicators. Some reports showed that a reduction of in BMI and hypoalbuminemia were related to the poor prognosis of malignancy, [26][27][28] while other reports showed that albumin levels and BMI were not independent prognostic indicators for OS. 29,30 Our results are congruent with the latter results.…”
Section: Discussionmentioning
confidence: 99%